A configuração de grupo econômico na justiça do trabalho - Garcia, Gabriella Cociolito (2018)
The purpose of this paper consists in point out the relevance of the economic groups in the Labor Area, examining their characteristics and legal implications from a sociological, economic and legal point of view in relation to the employer responsibility. The changes brought by Law No. 13467/2017, called as "Labor Reform", and the possible impacts that the new wording of Article 2, Paragraph 2 of the CLT may have in the current cases in law understanding. Finally, we will discuss the main models of grouping and other commercial relations that generate doubts about the existence or not of the same economic group, namely; Joint ventures, consortia, franchise agreements, trademark license agreements, cartels and joint venture companies ("SCPs")